Publication Strategy For Introducing The Batujaya Karawang Temple Complex in The Webtoon Design “Unur Batu” - Aidha Rohmalia; Muhammad Fauzi (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Most people in Indonesia do not know that the oldest temple in Indonesia is in Karawang Regency. The design of the Webtoon